Effect of Silver Nanoparticle Size on Antibacterial Activity - Vadim A. Ershov; Boris G. Ershov (Toxics)
The ubiquitous use of products containing AgNPs results in the entry of nanoparticles into the environment. Both nanoparticles and Ag+ released upon their oxidative dissolution have a toxic effect on living microorganisms. The antibacterial activity of spherical silver nanoparticles of 10.8 ± 0.8 nm and 22.7 ± 2.2 nm in size stabilized by carbonate ions was studied against Escherichia coli and other bacteria. The biocidal action of silver increases as the particle size decreases. Analysis of these results and other known data made it possible to substantiate a linear proportional relationship between the minimum inhibitory concentration (MIC) or the half-maximal inhibitory concentration (IC50) and silver nanoparticle size and determine empirical parameters for this relationship. The antibacterial activity (toxicity) is directly proportional to the specific surface area of nanosized silver.